Peningkatan Literasi Dan Numerasi Siswa Kelas IV Melalui Program Pojok Baca di SDN Aimitat, Desa Urungpigang, Kecamatan Wailiti - Karmila Karmila; Winda Winda; Ayuni Ayuni; Rimasi Rimasi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to increase students' Numeracy Literacy through a reading corner. This research was motivated by the low motivation of students in numeracy literacy at SDN Aimitat. Therefore, one of the first steps taken was to create a